MEDIA DYSFUNCTION ON THE COMMODIFICATION OF INDONESIAN HORROR FILMS - Ariestya, Vidya Talisa; Astuti, R.A. Vita (Universitas Katolik Soegijapranata, 2025)
The trend of horror films in the Indonesian film industry for 2019–2024 has given rise to a media dysfunction affected by the commodification of viral content. This is due to the lack of diversity, decreased quality, and deviation of cultural, religious, and ethical information from the films produced. The research conducted as a references for producers and content creators to address media dysfunction caused by the commodification of viral content. This method of this research uses a qualitative approach by interviewing Indonesian film industry players. The research results that the application of three appropriate types of commodification has the potential to better suppress media dysfunction compared to the application of virality. In addition to collaboration among all parties in the film industry, there needs to be awareness from producers in determining indicators of a film's success, beyond financial profit.